Antibiotics - Yes or No? - J E Mosier (Kansas Agricultural Experiment Station Research Reports, 1977)
From January, 1976, to January, 1977, I served as chairman of a subcommittee of the National Advisory Food &Drug Consultants charged with examining several issues concerned with the "Use of Antibiotics in Animal Feeds". It was through the activities of this subcommittee that I have had the opportunity to review papers and to hear presentations and discussions by many knowledgeable people concerning such use. Most of you are fully cognizant that the use of antibiotics in animal feeds originated from the observations of Jukes and Stokstad in 1949. Subtherapeutic levels are used for increasing weight gain, improving feed efficiency, and preventing or controlling animal disease. In 1973 in the United States, 20.8 million pounds of antibiotics were produced--12.6 million destined for medicinal use and 8.2 million pounds for nonmedical use, primarily in animal feeds.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Antibiotics; Subtherapeutic